2021
DOI: 10.3390/w13162175
|View full text |Cite
|
Sign up to set email alerts
|

Páramo Lakes of Colombia: An Overview of Their Geographical Distribution and Physicochemical Characteristics

Abstract: The páramo lakes, Colombia, situated in the neotropical region, are of great value both as natural heritage and as water source to the most populated areas of the Andes, but are threatened by expanding agriculture, livestock, mining, and landscape fragmentation. Nonetheless, a general assessment of the lakes’ distribution and biogeochemical characteristics was lacking. We made a complete inventory of the Colombian páramo lakes and characterized their morphometry and water chemistry based on a survey of 51 lake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
1
4
0
2
Order By: Relevance
“…These correlations might possibly reflect a stronger impact in smaller and shallower water bodies of soil-water inputs with a low NO 3 − content related to denitrification in highland soils (Pineda et al 2021). The NH 4 + and NO 3 − values we report in Ecuadorian lakes were consistent with those in 51 páramo lakes in the Colombian Andes investigated by Zapata et al (2021) who reported an average NH 4 + concentration of 36 µmol/L (range 20-60 µmol/L), and an average NO 3 − concentration of 1.1 µmol/L (range 0.1-12.8 µmol/L). The pCO 2 values ranged between 208 and 10,069 ppm (Fig.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…These correlations might possibly reflect a stronger impact in smaller and shallower water bodies of soil-water inputs with a low NO 3 − content related to denitrification in highland soils (Pineda et al 2021). The NH 4 + and NO 3 − values we report in Ecuadorian lakes were consistent with those in 51 páramo lakes in the Colombian Andes investigated by Zapata et al (2021) who reported an average NH 4 + concentration of 36 µmol/L (range 20-60 µmol/L), and an average NO 3 − concentration of 1.1 µmol/L (range 0.1-12.8 µmol/L). The pCO 2 values ranged between 208 and 10,069 ppm (Fig.…”
Section: Resultssupporting
confidence: 87%
“…These conditions have favored the formation of peat and a large number of wetlands and lakes. The páramo usually presents deep and organic rich soils (30% by volume) and its vegetation is dominated by grasslands (Zapata et al 2021).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Currently, high‐mountain lakes across the globe are considered sentinels of the systemic change of the planet (Moser et al 2019). In this context, there is a growing interest in tropical high‐mountain lakes (Michelutti et al 2015; Van Colen et al 2017; Benito et al 2019; Steinitz‐Kannan et al 2020; Zapata et al 2021), which have historically received less attention (Eggermont et al 2007). Although high‐mountain lakes are among the most comparable ecosystems globally, and a common conceptual framework might be used to analyze them (Catalan and Donato‐Rondón 2016), tropical high‐mountain lake regions have unique environmental characteristics that require special attention.…”
mentioning
confidence: 99%
“…Bedrock geology generates gradients of ions and buffering capacity in high mountains, as demonstrated in analyses from of a larger set of lakes within Cajas ( n = 165; Mosquera et al., 2022), in Colombia ( n = 51; Zapata et al., 2021), and in the Spanish Pyrenees ( n = 83; Rivera‐Rondón & Catalan, 2020). However, the role of weathering of volcanic bedrock on diatom distribution in tropical climates is not well‐known.…”
Section: Discussionmentioning
confidence: 98%
“…Páramos are wet alpine grasslands and shrublands that occur between ~2800 to 4700 m above sea level (a.s.l.) and extend from 11°N to 8°S latitude in the Andes of Venezuela, Colombia and Ecuador (Zapata et al., 2021). Despite their limited spatial extent, they are centres of exceptionally high levels of biodiversity and endemism (Antonelli et al., 2018; Rull, 2011).…”
Section: Introductionmentioning
confidence: 99%